A study on the influence of HIV related stigma and alcohol use on adherence to antiretroviral therapy among adults on treatment at the infectious disease care clinics in Princess Marina and Nyangabgwe referral hospitals in Botswana - Munyadzwe-Gabe, Grace (Stellenbosch : Stellenbosch University, 2008)
Thesis (MPhil (Industrial Psychology. Africa Centre for HIV/AIDS Management))--Stellenbosch University, 2008.